ENGINEERING COMPETENCIES DEVELOPMENT: A MANAGEMENT APPROACH TO TEACHING “AUTOMOTIVE ENGINEERING” - Duhanets, Viktor; Pukas, Vitalii; Volynkin, Mykola; Pecheniuk, Andrii (Public Management and Policy, 2025)
The article examines and comprehensively substantiates the urgent need to modernize educational programs by implementing a managerial approach to teaching engineering disciplines, particularly “Automobiles”, in modern Ukrainian universities. It provides a detailed analysis of traditional teaching methods, which primarily focus on transferring purely theoretical knowledge about the structure and operating principles of a car. The key shortcomings of this approach are identified: a significant gap between theoretical training and practical skills, a lack of interdisciplinary connections, and the insufficient development of critically important soft skills such as management, teamwork, and communication. The proposed educational model involves the phased and logical integration of managerial elements directly into the educational process. This allows students to harmoniously combine fundamental technical knowledge with skills in planning, organization, and control at every stage of mastering the material. The key tools for implementing this innovative model include project-based learning that simulates real engineering projects, case studies that facilitate the analysis of real-world production situations, and simulations that immerse students in the process of project management and problem-solving. The expected outcomes of implementing this managerial approach are significant: they include not only an increase in student motivation through a practical orientation but also the formation of comprehensive engineering and managerial skills. The ultimate result will be the preparation of graduates who are significantly better equipped to work in the real, dynamic conditions of the modern automotive industry and will possess a high level of competitiveness in the labor market.